Strikingly dissimilar effect of Mn and Zn dopants imposed on local structural distortion of Ba0.5K0.5Fe2As2 superconductor - Cheng, Jie (Journal of synchrotron radiation, 2013)
To clarify the contrasting impurity effects of Mn and Zn dopants on the critical temperature of optimally doped Ba0.5K0.5Fe2As2 superconductors, extended X-ray absorption fine-structure spectroscopy was implemented at the Fe and As K-edge. In Mn-doped compounds a gradual deviation of the symmetric FeAs4 tetrahedron and weakening of the Fe-As bond was observed. Conversely, in Zn-doped compounds the perfect FeAs4 tetrahedron is maintained and the Fe-As bond is rigid. The local structural details are consistent with the development of superconductivity in these two systems, suggesting a significant role played by the topology of the FeAs4 tetrahedron and rigidness of the Fe-As bond in Mn/Zn-doped Ba0.5K0.5Fe2As2 superconductors